INCREASING HUMAN RESOURCES (HR) IN THE IMPLEMENTATION OF STANDARD OPERATING PROCEDURES (SOP) FOR PUBLIC PEACE AND ORDER IN THE CIVIL SERVICE POLICE UNIT OF SOLOK CITY - Suhelmi Helia; Tetti Eka Dharma; Endra Endra; Budi Chandra; Willy Andi Eka Sandra (Jurnal Ekonomi, 2023)
Standard Operating Procedures (SOPs) that have been made very well, should be put to good use as well. This can be realized if the existing SOPs are always socialized and personnel have sufficient knowledge and skills to implement and apply SOPs optimally. Thus, the implementation of SOPs will run consistently and continuously, can be monitored and evaluated to improve service quality. This study aims to 1) Know the improvement of Human Resources (HR) of the Solok City Civil Service Police Unit, 2) Know the implementation of the Presedur Operational Standard (SOP) for peace and public order in the Solok City Civil Service Police Unit. This type of research uses a qualitative approach. Data collection techniques with observations, interviews, personal and official documents, photographs, recordings, drawings and informal conversations. The informant of this research is estimated to really know and be able to provide information about the implementation of the SOP of the Solok City Civil Service Police Unit using the Snowball technique. Steps in data analysis, namely data reduction, data presentation and conclusions. From this study, it was found that 1) the improvement of Human Resources (HR) of the Solok City Civil Service Police Unit was slow, this happened to the level of education and knowledge of Solok City Satuan Polisi Pamong Praja officers. 2) There is an implementation of the Presedur Operational Standard (SOP) for peace and public order in the Civil Service Police Unit of Solok City but it has not been optimal.